Validity of the Ages and Stages Questionnaire to detect risk of Developmental Coordination Disorder in preschoolers. (20th December 2015) - King‐Dowling, S.; Rodriguez, M. C.; Missiuna, C.; Cairney, J.
Abstract: Background: A reliable and valid screening tool for detecting children at risk for Developmental Coordination Disorder (DCD) is needed. The purpose of this study was to evaluate the ability of the Ages and Stages Questionnaire‐Third Edition (ASQ‐3) motor scales to detect children at risk for DCD in a community‐based sample of children aged 3.5–5.5 years. Methods: One hundred and sixty parent–child pairs were recruited from community‐based organizations. Children were eligible if they spoke English and had no known physical impairments. Eligible parents were asked to fill out the ASQ‐3, following which their child's fine motor and gross motor proficiency was assessed using the Movement Assessment Battery for Children – Second Edition (MABC‐2). DCD risk was defined as those children scoring at or below the 16th percentile on the MABC‐2. Sensitivity and specificity of the fine and gross motor areas of the ASQ‐3 were examined and referenced against the DCD risk classification. Results: The ASQ‐3 total motor score correlated moderately with overall standard score on the MABC‐2 ( r  = 0.41; p  < 0.001). Regardless of the ASQ‐3 cut‐off used, sensitivities of the ASQ‐3 fine motor or gross motor scale to detect DCD risk were low at 21–47%, whereas specificities were high at 89–96%. Conclusion: Early identification of motor skill delays is important in order to intervene and hopefully prevent the associated negative health consequences. However, because of the low sensitivity of the ASQ‐3 motor scales, these results suggest that the ASQ‐3 is not an appropriate screening tool to identify children at risk for DCD in the preschool population.